2022
DOI: 10.3390/antiox11081440
|View full text |Cite
|
Sign up to set email alerts
|

Increased Adherence to the Mediterranean Diet after Lifestyle Intervention Improves Oxidative and Inflammatory Status in Patients with Non-Alcoholic Fatty Liver Disease

Abstract: Background: A Mediterranean diet (MedDiet) is recommended as a therapy for non-alcoholic fatty liver disease (NAFLD) because there is no specific pharmacological treatment for this disease. Objective: To assess the relationship between the adherence to the Mediterranean diet and the intrahepatic fat content (IFC), levels of oxidative stress, and inflammation biomarkers after a 6-month lifestyle intervention in NAFLD patients. Methods: Patients diagnosed with NAFLD (n = 60 adults; 40–60 years old) living in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 74 publications
(73 reference statements)
2
9
0
Order By: Relevance
“…High MPO levels are associated with an increment of oxidative stress and inflammation which are characteristic of overweight and obesity [ 39 ]. Our results are in accordance with others studies showing that a better AMD and an increase in physical activity ameliorate the inflammatory profile and, therefore, decrease the levels of MPO [ 40 , 41 ]. Omentin is an anti-inflammatory adipokine mainly expressed and secreted from visceral adipose tissue [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…High MPO levels are associated with an increment of oxidative stress and inflammation which are characteristic of overweight and obesity [ 39 ]. Our results are in accordance with others studies showing that a better AMD and an increase in physical activity ameliorate the inflammatory profile and, therefore, decrease the levels of MPO [ 40 , 41 ]. Omentin is an anti-inflammatory adipokine mainly expressed and secreted from visceral adipose tissue [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…In all of these, we found a significant improvement in both the mean values obtained at the baseline visit and at 12 months, as well as in the prevalence of high risk before and after the diet. This is of vital importance, since there are currently no drugs approved for the treatment of NAFLD, as dietary intervention and physical exercise have been shown to be effective in the treatment of NAFLD [ 72 , 73 , 74 , 75 ]. It is worth highlighting the values achieved in the very significant decrease in the high risk of liver fibrosis, obtained in both men and women: BAAT high of −32.4% for the former and −26.6% for the latter.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with a previous study evidencing high levels of enzymatic activity of catalase and SOD in plasma from patients with high cardiovascular risk after an intervention with the MedDiet [ 65 ]. Moreover, it was observed that after 6 months of lifestyle intervention, IL-6 and TNFα were decreased, although only significantly for IL-6 in the group with high adherence to the MedDiet [ 14 ]. Some of the beneficial effects of the MedDiet are related to the presence of bioactive compounds with antioxidant and anti-inflammatory activity [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high adherence to the MedDiet is related to better values of intrahepatic fat content (IFC) in NAFLD patients and a better status of MetS characteristics, such as high decreases in body weight, body mass index (BMI), and blood pressure [ 13 ]. A high adherence to the MedDiet is associated with high improvements in the proinflammatory and pro-oxidative status and the cardiorespiratory fitness of NAFLD patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%